Música rap: narrativa dos jovens da periferia de Teresina - Silva, Antonio Leandro da (2006)
The present composition has as a center Rap Music analysis; it is understood as a young people narrative from the suburb of Teresina. The option for this subject it is directly tied with my experiences, as Franciscan religious, experiences that were lived in the suburb of this city, where I knew Hip Hop Movement. During six years, I could see, feel and hear daily realities lived by these citizens, and notice as Rap became the greater power element and valorization inside Hip-Hop Movement, besides it regains the word through rappers narratives. A research, based on excellent theoretical issue about "memory" and "narrative", most in Benjamin s Theory, shows that Rap is the "new contemporary form of narrative". This is for two reasons: First, because being from an African matrix music, Rap rescues the "reminiscence", "saving" the word, i.e. the way to tell histories lived deeply in a collective way; Second, it brings back word "Redemption", because it rescues what it had been denied to us: the speech. In this, materializes the "authentic experience" (Erfahrung), therefore, breaking up "time continuous flow of "history continuum" - when we talk about oppressors history - the oppressed ones gain voice and they build a new history. Because of this, the tradition of the oppressed ones is necessarily intermittent. Report here, it means to tell, to mention daily events of a community life from a group, a culture, a folk. Paraphrasing Benjamin, rappers start their narrative with a description of facts that will improvise (speak), attributing them their own experience of life. The "work of ethnographic field" becomes a "way to produce knowledge" (Geertz, 1989), from an intense involvement with the researched groups. This was my adventure during the time of field research: to hear the old "plays nonspeaking part" (Dias, 1998) that hadn t nor voice, nor who listen to them. Thus, after analyzing socio-economics and geographic changes Teresina city had suffered in 80th and 90th decades, I rebuilt interviewed citizens past through its narratives, resource that assisted to open memory s windows. Therefore I opted to verbal history of life as qualitative technique because it tries to restore, through the involved citizens vision, a period or historical event. Thus, by this technique, it had been collected data that are related to different moments toward which young people had passed through; at the same time, I tried to identify youthful sociability spaces, Hip-Hop movement consolidation and its implications in building ethnic identities of these young people